2003
DOI: 10.1046/j.1365-2265.2003.01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the intracellular mechanisms mediating somatostatin and lanreotide inhibition of DNA synthesis and growth hormone release from dispersed human GH‐secreting pituitary adenoma cells in vitro

Abstract: These data show that somatostatin and lanreotide inhibit human GH-secreting pituitary adenoma cell proliferation and hormone release in vitro, and suggest that the activation of tyrosine phosphatases may represent intracellular signals mediating the antiproliferative effects and that the inhibition of the voltage-dependent calcium channels and adenylyl cyclase activities may control GH secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 57 publications
4
28
1
1
Order By: Relevance
“…Consistent with this, several authors have described that patients bearing tumors with the highest SSTR2 expression respond better to SA treatment in terms of hormonal control (19)(20)(21)23). Some groups have also studied the in vitro anti-proliferative action of SA and its correlation with the tumor SSTR expression pattern (26)(27)(28). Somatostatin, lanreotide, SSTR1, SSTR2, and SSTR5 ligands (BIM-23926, BIM-23190, and BIM-23268) have been shown to effectively reduce cell viability (26,27).…”
Section: Introductionmentioning
confidence: 66%
“…Consistent with this, several authors have described that patients bearing tumors with the highest SSTR2 expression respond better to SA treatment in terms of hormonal control (19)(20)(21)23). Some groups have also studied the in vitro anti-proliferative action of SA and its correlation with the tumor SSTR expression pattern (26)(27)(28). Somatostatin, lanreotide, SSTR1, SSTR2, and SSTR5 ligands (BIM-23926, BIM-23190, and BIM-23268) have been shown to effectively reduce cell viability (26,27).…”
Section: Introductionmentioning
confidence: 66%
“…SRIF is associated with increased protein phosphatase activity in both human GH-secreting pituitary adenoma cells and rat cell lines as well as human non-functioning pituitary tumors (Cervia & Bagnoli 2007). SRIF increases tyrosine phosphatase activity and was associated with the inhibition of cell growth in human GH-secreting pituitary tumor cells in vitro (Florio et al 2003), while serine/threonine phosphatase activity participates in SRIF-mediated regulation of Ca 2C influx through dephosphorylation of Ca 2C and K C voltage-activated (BK) channels (White et al 1991).…”
Section: Protein Phosphatase Pathwaysmentioning
confidence: 99%
“…All the five genes are expressed in normal adult human pituitaries, however, SSTR4 mRNA is found at extremely low levels (15,16). Somatostatin receptors expression in pituitary adenomas is reported to be highly variable within and between tumor subtypes (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). In studies conducted with non-pituitary tissues, all SSTR subtypes have been shown to have anti-proliferative effects in some cell types and SSTR2 and SSTR3 were specifically shown to initiate apoptosis (34).…”
Section: Introductionmentioning
confidence: 99%